Super Rhotrix Driven Multi-criteria Decision Making - R. Priya; Nivetha Martin; Florentine Smarandache (Journal of Analytical Uncertainty, 2025)
This study introduces the theoretical conceptualization of Super Rhotrix and its applications in multi-criteria decision making. The properties, operations and classifications of Super Rhotrix are discoursed in this work. The geometrical interpretation of the structures of rhotrix and super rhotrix are described in the context of applications to decision-making. The rigidity and compatibility of super rhotrix is well -substantiated and demonstrated with the illustration of supplier selection problem. The merits and limitations of the proposed decision-making approach is also discussed.